EXPLORING HAPPINESS IN THE WORKPLACE AMONG SCHOOL TEACHERS: AN ORGANIZATIONAL PSYCHOLOGY PERSPECTIVE - Arina Nur Hikmah; Rosita Endang Kusmaryani; Clayton Michael Fonceca (Psyche: Jurnal Psikologi, 2026)
Teachers happiness at work remains underexplored within a phenomenological framework, particularly regarding how teachers interpret happiness in their everyday professional lives. This study aims to address this gap by examining the construction of teachers lived experiences of happiness at work. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with three junior high school teachers with a minimum of two years of teaching experience. Data were analyzed using Miles and Hubermans analysis model to ensure systematic, consistent, and credible interpretation of participants experiences. The findings reveal that teachers happiness at work is shaped by three interrelated conceptual clusters: meaning-oriented factors (such as personal meaning, purpose, motivation, and subjective perceptions of happiness), relational factors (including social support, collegial relationships, enthusiasm, and emotional engagement), and organizational factors (encompassing career development opportunities, job satisfaction, challenges and coping strategies, as well as perceptions of an ideal organizational environment). Overall, the study highlights that teachers happiness at work is a multidimensional and subjective construct, predominantly grounded in meaningful work, a supportive workplace, and positive social relationships rather than material conditions.